Flourishing enterprise : the new spirit of business - Laszlo, Christopher, ....-; Brown, Judy, 1945-; Ehrenfeld, John, ....- (Stanford : Stanford University Press, 2014)
The notion of responsible business has infiltrated our markets, and going green is now a part of our mindset. But, sustainability as we know it is not enough. Flourishing-the aspiration that humans and life in general will thrive on the planet forever-should be a key goal for every business today. This is a bold concept, like sustainability was a decade ago. Just as sustainability has become a matter of course, so too will flourishing become a cornerstone of business tomorrow.How are companies to attain this big-picture goal? Drawing together decades of research along with in-depth interviews, Flourishing Enterprise argues that many strategic, organizational, and operational efforts to be sustainable reach the potential of flourishing when they incorporate one additional ingredient: reflective practices. Offering more than a dozen such practices, this book leads readers down a path to greater business success, personal well-being, and a healthier planet.Readers will find that adding reflective practices to existing business efforts does not require more work; it simply changes the way we do our work and, more importantly, the results we achieve. Cultivating emotional and spiritual health is the next frontier; this future-oriented guide develops these core competencies while stretching the ongoing conversation about profitable, sustainable business.
Includes bibliographical references and index.
Keywords: Industrial management -- Moral and ethical aspects; Organisatiekunde; Organisaties; Social responsibility of business; Spirituality